2009
DOI: 10.1111/j.1600-9657.2009.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Biological restoration’: total crown anterior

Abstract: Restorative odontology is in constant evolution and is constantly seeking more aesthetic solutions to attend to demands from patients in search of the perfect smile. The case study presented herein refers to the aesthetic and functional recuperation of dental element 21, through the use of a dental fragment obtained through an extracted tooth, a technique known as 'Biological Restoration'. The results obtained, which were highly satisfactory, lead one to conclude that this technique can be considered as an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 5 publications
2
26
0
1
Order By: Relevance
“…Careful attention should be given to this problem, which is a great challenge in the modern restorative dentistry. [5,11,12] Due to fracture of maxillary central incisors, some treatments may be suggested, such as removal of the fragment, followed by restoration, [13] allogeneic collage, [2,6,8,[13][14][15][16] increased clinical crown, [13,17] orthodontic extrusion (with or without gingivoplasty), [13] extraction, followed by implant and/or conventional fixed prostheses. [13,17] In a young patient, some factors must be considered, such as occlusion, hygiene, treatment time, incomplete bone growth and tooth eruption, longevity, need to change the restoration over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Careful attention should be given to this problem, which is a great challenge in the modern restorative dentistry. [5,11,12] Due to fracture of maxillary central incisors, some treatments may be suggested, such as removal of the fragment, followed by restoration, [13] allogeneic collage, [2,6,8,[13][14][15][16] increased clinical crown, [13,17] orthodontic extrusion (with or without gingivoplasty), [13] extraction, followed by implant and/or conventional fixed prostheses. [13,17] In a young patient, some factors must be considered, such as occlusion, hygiene, treatment time, incomplete bone growth and tooth eruption, longevity, need to change the restoration over time.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that dental trauma corresponds to 18% of all injuries occurred in children at preschool age. [1] According to Tavano et al, 2009, [2] almost 79% of children between 9 and 14 years have suffered some type of dental injury. This fact is related to the practice of sports and leisure activities, functional and psychological problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Various other authors have successfully used such biological posts to restore fractured tooth. 1,2,11 However there are certain limitations, such as finding teeth with proper bulk, color, and patients refusal to treatment. 2,11 This case report describes the dentinal post made from natural extracted sterilized tooth for restoration of fractured anterior tooth.…”
Section: Introduction:-mentioning
confidence: 99%
“…6 Several authors have suggested the use of natural teeth fragments as an efficient method for restoring fractured anterior teeth. 6,7 When the patient presents the fragment in good condition, this procedure presents optimal results in the restoration of fractured teeth (autogenous bonding). 6,8,9 However, when the patient does not present the fragment, or its use is not recommended, donated extracted teeth (homogeneous bonding) can be used.…”
Section: Introductionmentioning
confidence: 99%